AuBr3-catalyzed azidation of per-O-acetylated and per-O-benzoylated sugars - Rajput, Jayashree; Hotha, Srinivas; Vangala, Madhuri (Beilstein Journal of Organic Chemistry, 2018)
Herein we report, for the first time, the successful anomeric azidation of per-O-acetylated and per-O-benzoylated sugars by catalytic amounts of oxophilic AuBr3 in good to excellent yields. The method is applicable to a wide range of easily accessible per-O-acetylated and per-O-benzoylated sugars. While reaction with per-O-acetylated and per-O-benzoylated monosaccharides was complete within 1–3 h at room temperature, the per-O-benzoylated disaccharides needed 2–3 h of heating at 55 °C.
Keywords: acylated sugars; azidation; gold(III) bromide; N-glycoside; oxophilicity

(untitled) - Li, X.; Zhu, J. (Eur. J. Org. Chem., 2016)

(untitled) - Dorel, R.; Echavarren, A. M. (Chem. Rev., 2015)

(untitled) - Hashmi, A. S. K.; Hutchings, G. J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Fürstner, A.; Davies, P. W. (Angew. Chem., Int. Ed., 2007)

(untitled) - Hashmi, A. S. K. (Chem. Rev., 2007)

(untitled) - Morita, N.; Yasuda, A.; Shibata, M.; Ban, S.; Hashimoto, Y.; Okamoto, I.; Tamura, O. (Org. Lett., 2015)

(untitled) - Hotha, S.; Kashyap, S. (J. Am. Chem. Soc., 2006)

(untitled) - Li, Y.; Yang, Y.; Yu, B. (Tetrahedron Lett., 2008)

(untitled) - Mamidyala, S. K.; Finn, M. G. (J. Org. Chem., 2009)

(untitled) - Kayastha, A. K.; Hotha, S. (Chem. Commun., 2012)

(untitled) - Sureshkumar, G.; Hotha, S. (Tetrahedron Lett., 2007)

(untitled) - Li, Y.; Yang, X.; Liu, Y.; Zhu, C.; Yang, Y.; Yu, B. (Chem. – Eur. J., 2010)

(untitled) - Tang, Y.; Li, J.; Zhu, Y.; Li, Y.; Yu, B. (J. Am. Chem. Soc., 2013)

(untitled) - Zhu, Y.; Yu, B. (Chem. – Eur. J., 2015)

(untitled) - Adhikari, S.; Baryal, K. N.; Zhu, D.; Li, X.; Zhu, J. (ACS Catal., 2013)

(untitled) - Koppolu, S. R.; Niddana, R.; Balamurugan, R. (Org. Biomol. Chem., 2015)

(untitled) - Roy, R.; Rajasekaran, P.; Mallick, A.; Vankar, Y. D. (Eur. J. Org. Chem., 2014)

(untitled) - Götze, S.; Fitzner, R.; Kunz, H. (Synlett, 2009)

(untitled) - Vidadala, S. R.; Hotha, S. (Chem. Commun., 2009)

(untitled) - Vibhute, A. M.; Dhaka, A.; Athiyarath, V.; Sureshan, K. M. (Chem. Sci., 2016)

(untitled) - Peng, P.; Schmidt, R. R. (J. Am. Chem. Soc., 2015)

(untitled) - Roy, R.; Palanivel, A. K.; Mallick, A.; Vankar, Y. D. (Eur. J. Org. Chem., 2015)

(untitled) - Zhang, Q.; Sun, J.; Zhu, Y.; Zhang, F.; Yu, B. (Angew. Chem., Int. Ed., 2011)

(untitled) - Rao, B. V.; Manmode, S.; Hotha, S. (J. Org. Chem., 2015)

(untitled) - Mishra, B.; Neralkar, M.; Hotha, S. (Angew. Chem., Int. Ed., 2016)

(untitled) - Kayastha, A. K.; Hotha, S. (Beilstein J. Org. Chem., 2013)

(untitled) - Mallick, A.; Mallikharjunarao, Y.; Rajasekaran, P.; Roy, R.; Vankar, Y. D. (Eur. J. Org. Chem., 2016)

(untitled) - Tomabechi, Y.; Squire, M. A.; Fairbanks, A. J. (Org. Biomol. Chem., 2014)

(untitled) - Bianchi, A.; Bernardi, A. (J. Org. Chem., 2006)

(untitled) - Doores, K. J.; Mimura, Y.; Dwek, R. A.; Rudd, P. M.; Eliott, T.; Davis, B. G. (Chem. Commun., 2006)

(untitled) - Dedola, S.; Nepogodiev, S. A.; Field, R. A. (Org. Biomol. Chem., 2007)

(untitled) - Kasuya, M. C. Z.; Wang, L. X.; Lee, Y. C.; Mitsuki, M.; Nakajima, H.; Miura, Y.; Sato, T.; Hatanaka, K.; Yamagata, S.; Yamagata, T. (Carbohydr. Res., 2000)

(untitled) - Pal, A. P. J.; Vankar, Y. D. (Tetrahedron Lett., 2010)

(untitled) - Pal, A. P. J.; Kadigachalam, P.; Mallick, A.; Doddi, V. R.; Vankar, Y. D. (Org. Biomol. Chem., 2011)

(untitled) - Lim, D.; Brimble, M. A.; Kowalczyk, R.; Watson, A. J. A.; Fairbanks, A. J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Meldal, M.; Tornøe, C. W. (Chem. Rev., 2008)

(untitled) - Korytnyk, W.; Mills, J. A. (J. Chem. Soc., 1959)

(untitled) - Martichonok, V.; Whitesides, G. M. (J. Org. Chem., 1996)

(untitled) - Baluja, G.; Chase, B. H.; Kenner, G. W.; Todd, A. (J. Chem. Soc., 1960)

(untitled) - Nolte, R. J. M.; van Zomeren, J. A. J.; Zwikker, J. W. (J. Org. Chem., 1978)

(untitled) - Lee, D. J.; Mandal, K.; Harris, P. W. R.; Brimble, M. A.; Kent, S. B. H. (Org. Lett., 2009)

(untitled) - Györgydeák, Z.; Thiem, J. (Carbohydr. Res., 1995)

(untitled) - Tropper, F. D.; Anderson, F. O.; Braun, S.; Roy, R. (Synthesis, 1992)

(untitled) - Soli, E. D.; Manoso, A. S.; Patterson, M. C.; DeShong, P. (J. Org. Chem., 1999)

(untitled) - Nepogodiev, S. A.; Dedola, S.; Marmuse, L.; de Oliveira, M. T.; Field, R. A. (Carbohydr. Res., 2007)

(untitled) - Tosin, M.; Murphy, P. V. (Org. Lett., 2002)

(untitled) - Paulsen, H. (Adv. Carbohydr. Chem. Biochem., 1971)

(untitled) - Györgydeák, Z.; Szilágyi, L.; Paulsen, H. (J. Carbohydr. Chem., 1993)

(untitled) - Marzag, H.; Alaoui, S.; Amdouni, H.; Martin, A. R.; Bougrin, K.; Benhida, R. (New J. Chem., 2015)

(untitled) - Lepage, M. L.; Bodlenner, A.; Compain, P. (Eur. J. Org. Chem., 2013)

(untitled) - Tanaka, T.; Nagai, H.; Noguchi, M.; Kobayashia, A.; Shoda, S.-i. (Chem. Commun., 2009)

(untitled) - Pilgrim, W.; Murphy, P. V. (J. Org. Chem., 2010)

(untitled) - Salunke, S. B.; Babu, N. S.; Chen, C.-T. (Chem. Commun., 2011)

(untitled) - Vangala, M.; Shinde, G. P. (Beilstein J. Org. Chem., 2015)

(untitled) - Vangala, M.; Shinde, G. P. (Beilstein J. Org. Chem., 2016)

(untitled) - Vangala, M.; Dhokale, S. A.; Gawade, R. L.; Pattuparambil, R. R.; Puranik, V. G.; Dhavale, D. D. (Org. Biomol. Chem., 2013)